ROLE OF ASSESSMENT FRAMEWORKS IN DETERMINING PERFORMANCE OF ENTERPRISES A Case Study using LESAT Framework - George, Jomy Abraham (2011)
The research was carried out to analyze the existing Lean assessment frameworks and explore their role in organizational performance. In this endeavor, four business models Malcolm Baldrige National Quality Award (MBNQA), European Foundation for Quality Management (EFQM), Shingo Prize for Operational Excellence and Lean Enterprise Self Assessment Tool (LESAT) were contemplated and adopted to derive conclusions. The overall scrutiny of the frameworks pointed out the fact that there are tremendous learning opportunities in the form of finding „hidden spots‟ or areas of improvement once the assessment is conducted. Moreover, the invaluable feedback from the assessments proved to be an overwhelming factor which most managers of enterprises support. The findings reveal that besides the companywide deficiencies, it takes into account the best practices which the models encourage to share within the enterprise and extended enterprise.